2020
DOI: 10.1186/s13072-020-00345-9
|View full text |Cite
|
Sign up to set email alerts
|

Linker histone epitopes are hidden by in situ higher-order chromatin structure

Abstract: Background: Histone H1 is the most mobile histone in the cell nucleus. Defining the positions of H1 on chromatin in situ, therefore, represents a challenge. Immunoprecipitation of formaldehyde-fixed and sonicated chromatin, followed by DNA sequencing (xChIP-seq), is traditionally the method for mapping histones onto DNA elements. But since sonication fragmentation precedes ChIP, there is a consequent loss of information about chromatin higherorder structure. Here, we present a new method, xxChIP-seq, employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
3
4
0
Order By: Relevance
“…Common nucleosomes were characterised by DNA methylation enrichment, while shifted nucleosomes were depleted of DNA methylation (Figure 4B). This is consistent with previous reports that DNA methylation stabilises nucleosomes while de-methylation or hydroxymethylation makes nucleosomes more MNase-sensitive (39,51,52).…”
Section: Dependence Of Nucleosome Sensitivity To Mnase Digestion In T...supporting
confidence: 93%
See 1 more Smart Citation
“…Common nucleosomes were characterised by DNA methylation enrichment, while shifted nucleosomes were depleted of DNA methylation (Figure 4B). This is consistent with previous reports that DNA methylation stabilises nucleosomes while de-methylation or hydroxymethylation makes nucleosomes more MNase-sensitive (39,51,52).…”
Section: Dependence Of Nucleosome Sensitivity To Mnase Digestion In T...supporting
confidence: 93%
“…Common nucleosomes were characterised by DNA methylation enrichment, while shifted nucleosomes were depleted of DNA methylation (Figure 3B). This is 13 consistent with previous reports that DNA methylation stabilises nucleosomes while demethylation or hydroxymethylation makes nucleosomes more MNase-sensitive (Teif et al 2014;Wiehle et al 2019;Teif et al 2020). The overall distribution of DNA fragments protected from MNase digestion was more enriched with shorter sizes in cancer in comparison with normal samples (Supplemental Figure S3).…”
Section: Dependence Of Nucleosome Sensitivity To Mnase Digestion In T...supporting
confidence: 91%
“…H3K27me3 levels correlate directly with the chromatin occupancy of histone H1 8 , 35 , an abundant protein family that binds dynamically to nucleosomes 36 and stabilizes chromatin compaction 8 . Previous ChIP analyses indicated that H1 is evenly distributed throughout the nucleus but shows low chromatin occupancy at TSS 37 , 38 . Our ChIP analyses do not show statistically significant differences between WT and DKO in H1 occupancy at a particular site; however, the aggregate plots indicate a marginally higher occupancy of H1 at enhancers and promoters in DKO, as compared to WT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…H3K27me3 levels correlate directly with the chromatin occupancy of histone H1 (Kim et al 2015b; Fyodorov et al 2018), an abundant protein family that binds dynamically to nucleosomes (Catez et al 2006) and stabilizes chromatin compaction (Fyodorov et al 2018). Previous ChIP analyses indicated that H1 is evenly distributed throughout the nucleus but shows low chromatin occupancy at TSS (Cao et al 2013; Teif et al 2020). Our ChIP analyses do not show statistically significant differences between WT and DKO in H1 occupancy at a particular site; however, the aggregate plots indicate a marginally higher occupancy of H1 at enhancers and promoters in DKO, as compared to WT regulatory regions (Fig.…”
Section: Resultsmentioning
confidence: 99%